2015
DOI: 10.1515/rem-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Academic Social Networks: How the web is changing our way to make and communicate researches

Abstract: Networking is not only essential for success in academia, but it should also be seen as a natural component of the scholarly profession. Research is typically not a purely individualistic enterprise. Academic social network sites give researchers the ability to publicise their research outputs and connect with each other. This work aims to investigate the use done by Italian scholars of 11/D2 scientific field. The picture presented shows a realistic insight into the Italian situation, although since the phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
6
0
4
Order By: Relevance
“…Her iki site de, kullanıcıların diğer kullanıcıların ağ etkinliğini izleyebilecekleri, yayınlarını, soru ve cevaplarını ekleyebilecekleri özelliklere sahiptir. Bu sitelerde kullanıcılar profiller oluşturur, ortak yazarları belirler, makalelerini ekler ve verimli araştırma işbirlikleri geliştirir (Bonaiuti, 2015).…”
Section: Hemunclassified
See 1 more Smart Citation
“…Her iki site de, kullanıcıların diğer kullanıcıların ağ etkinliğini izleyebilecekleri, yayınlarını, soru ve cevaplarını ekleyebilecekleri özelliklere sahiptir. Bu sitelerde kullanıcılar profiller oluşturur, ortak yazarları belirler, makalelerini ekler ve verimli araştırma işbirlikleri geliştirir (Bonaiuti, 2015).…”
Section: Hemunclassified
“…Referans yönetim siteleri okuyuculara odaklanıp, kullanıcıların çalışmaları için ilgili referansları bulmasına, toplamasına ve paylaşmasına yardımcı olurken, Academia.edu ve ResearchGate daha çok araştırma üreticilerine odaklanır (Bonaiuti, 2015).…”
Section: Mendeleyunclassified
“…While the authors concluded that the various services had reached critical mass within their university, they did not investigate the primary motivations for academics having joined. Similarly, Bonaiuti’s (2015) study of 260 Italian scholars in pedagogy, as identified by the nation’s scientific discipline classification system, revealed widespread use of ASNS, ‘…although it is not easy to identify in detail the reasons whereby some researchers seem to be more active than others’ (Bonaiuti, 2015: 9).…”
Section: Related Researchmentioning
confidence: 99%
“…An ASNS is a type of internet service that facilitates communication between researchers [7], shares scientific resources (news, reports, articles, and data sets), exchanges research opinions, and informs about the current research trend [8]. In addition to publishing researchers' work and facilitating personal exchanges, ASNSs are tools for describing organizational information and researcher interests [9].…”
Section: Introductionmentioning
confidence: 99%